2004
DOI: 10.1016/j.asj.2004.04.005
|View full text |Cite
|
Sign up to set email alerts
|

?Extreme? cosmetic surgery: a retrospective study of morbidity in patients undergoing combined procedures*1

Abstract: The results of this retrospective review do not indicate that the combination of cosmetic surgical procedures increases morbidity. The potential benefits of combined procedures may be considered with the expectation of comparably low complication rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…It has proven feasible to combine breast surgery with abdominoplasty provided that operating room time is minimized and appropriate logistical precautions are taken. This conclusion is consistent with the vast majority of literature on the topic of combining abdominoplasty with additional procedures (Table 1), 2,[6][7][8][12][13][14][19][20][21][22][23]65,72 including recent American Association for Accreditation of Ambulatory Surgery Facilities data 34 demonstrating that abdominoplasty plus one additional procedure is performed slightly more frequently than abdominoplasty alone (187,847 versus 176,092 cases, respectively), but abdominoplasty plus one, two, or three procedures is performed over 1.5 times more frequently than abdominoplasty alone (286,742 versus 176,092 cases, respectively). Critical elements in avoiding pitfalls include careful patient selection, meticulous but efficient operative planning and technique, a well-thought-out operative sequence accounting for necessary changes in patient position, close attention to fluid management, and a well-thought-out postoperative care plan that includes early ambulation.…”
Section: Impressions and Recommendations From Our Experiencesupporting
confidence: 91%
See 1 more Smart Citation
“…It has proven feasible to combine breast surgery with abdominoplasty provided that operating room time is minimized and appropriate logistical precautions are taken. This conclusion is consistent with the vast majority of literature on the topic of combining abdominoplasty with additional procedures (Table 1), 2,[6][7][8][12][13][14][19][20][21][22][23]65,72 including recent American Association for Accreditation of Ambulatory Surgery Facilities data 34 demonstrating that abdominoplasty plus one additional procedure is performed slightly more frequently than abdominoplasty alone (187,847 versus 176,092 cases, respectively), but abdominoplasty plus one, two, or three procedures is performed over 1.5 times more frequently than abdominoplasty alone (286,742 versus 176,092 cases, respectively). Critical elements in avoiding pitfalls include careful patient selection, meticulous but efficient operative planning and technique, a well-thought-out operative sequence accounting for necessary changes in patient position, close attention to fluid management, and a well-thought-out postoperative care plan that includes early ambulation.…”
Section: Impressions and Recommendations From Our Experiencesupporting
confidence: 91%
“…2,[19][20][21][22] Stevens et al report no increase in complications when comparing isolated abdominoplasty to abdominoplasty combined with breast surgery or facial rejuvenation. 2,20 They report a revision rate of 13 percent for these combined procedures, and note that although a 13 percent revision rate is not insignificant, 100 percent of these patients would have required a second operation should their procedures have been staged from the outset. 21 Although the breasts and the abdomen are anatomically distinct with regard to operative intervention, they are physiologically linked.…”
Section: Combining Abdominoplasty With Anatomically Distant Procedurementioning
confidence: 96%
“…Nevertheless, many combined plastic surgery procedures are routinely and safely performed in ambulatory surgery settings. Although studies that support the feasibility and safety of performing multiple simultaneous surgical procedures in the ambulatory setting are scarce and limited to the office-based setting, 77,78 these findings are corroborated by additional studies carried out in nonambulatory or unknown surgical settings that identified no statistically significant differences in complication rates between single and multiple procedures (i.e., abdominoplasty with or without other procedures). 79 -81 Despite the general safety of performing multiple surgical procedures in concert, certain patient factors have been correlated with an increased complication rate during multiple procedures, most notably, elevated body mass index.…”
Section: Multiple Proceduresmentioning
confidence: 78%
“…Given the financial incentive to the patient as well as having to endure only one postoperative recovery, it is not surprising that combined procedures are offered more frequently by plastic surgeons. 43,44 Safety of these procedures remains a main concern, particularly in the elective aesthetic surgery population. Our analysis identified 1180 hematomas, of which 473 (40.1%) occurred in patients who underwent combined procedures.…”
Section: Risk Factorsmentioning
confidence: 99%